(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aflatoxins (AFs), the poly-substituted bi-furanocoumarins, are the secondary metabolites of parasiticus/flavus group of Aspergillus genus. AFs including aflatoxin B1 (AFB1) have been classified under Class I Human Carcinogen by the International Agency for Research on Cancer (IARC) based on its potential hepatotoxic, nephrotoxic, mutagenic, genotoxic and immunotoxic nature. Cell injury caused by AFB1 are associated with consequences of the lipid peroxidation due to the release of free radicals and thereby damaging the biological systems. It is evident that since all the cell membranes are highly rich in polyunsaturated fatty acids (PUFAs) that could act as the substrates for such reactions. The most vital among such reactions is the AFB1-induced oxidative stress and its consequent generation og reactive oxygen species (ROS) and the oxidative DNA damage. Normally AFB metabolites produced under phase 1 metabolism would pass through the Phase 2 metabolism via., glutathione-S-transferase (GST) enzymatic processes allowing further detoxification and elimination of the toxin from the human system. This review is mainly to focus the role of antioxidants in metabolizing the AFB1 and thereby preventing the free radical induced peroxidation to prevent the predisposition of normal hepatocytes into malignant.